The Relationship Between Stress Levels of Pregnant Women and the Incidence of Premature Birth in the Work Area of ​​Dr. Hi Zainal Umar Sidiki Regional Hospital, North Gorontalo Regency - Sriyolanda Giasi; Anik Sri Purwanti (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Premature birth remains a major public health concern due to its strong association with increased neonatal morbidity and mortality. One of the contributing factors identified is maternal stress during pregnancy, which can negatively affect fetal development and potentially trigger early labor. Previous studies have shown that high stress levels in pregnant women may lead to hormonal imbalances, increased uterine activity, and other physiological changes that elevate the risk of preterm birth. Therefore, understanding the relationship between maternal stress and premature birth is essential for developing effective preventive strategies and improving maternal and neonatal outcomes. This study aimed to examine the relationship between stress levels in pregnant women and the incidence of premature birth in the working area of Dr. Hi Zainal Umar Sidiki Regional Hospital, North Gorontalo Regency. The research used an analytical observational design with a cross-sectional approach. A total of 30 pregnant women were selected using purposive sampling techniques. Maternal stress levels were measured using a validated questionnaire, while premature birth incidence was determined based on gestational age at delivery. Data were analyzed using the Wilcoxon signed-rank test with a significance level of p < 0.05. The results showed a significant relationship between maternal stress and premature birth (p = 0.000), indicating that higher stress levels increase the risk of preterm delivery. These findings highlight the importance of stress management, counseling, and comprehensive antenatal care.